Clinical manifestations of childhood asthma persisting until the age of seven - Rini Asterina; Sjawitri P Siregar; Bambang Madiyono; Bambang Supriyatno (Indonesian Pediatric Society Publishing House, 2016)
Background Asthma is a chronic illness commonly found in chil- dren. We aimed to find out the clinical manifestations of childhood asthma persisting until the age of seven and the influencing factors. Methods A review was performed at the outpatient clinic of the Department of Child Health Cipto Mangunkusumo Hospital Jakarta, from January 1992 to December 2001, on children with asthma who still had symptoms until the age of seven. Results During the period of 10 years, there were 322 children with clinical symptoms of asthma persisting until the age of 7. One hundred and forty-six (45.3%) met the inclusion criteria, consisting of 75 (51.4%) boys and 71 (48.6%) girls. The average age was 11.7 years. There were 101 (69.2%) patients with rare episodic asthma, 26.0% with frequent episodic asthma, and 4.8% with per- sistent asthma. Age of onset was mostly beyond 3 year-old (51%). Besides asthma, atopic diseases noted in these patients were al- lergic rhinitis in 85 (58.2%) and atopic dermatitis in 42 (28.8%). Logistic regression found that cigarette smoke exposure (adjusted OR 4.72, 95%CI 2.05;10.87, p=0.000), allergic rhinitis (adjusted OR 3.44, 95%CI 1.40;8.45, p=0.007), and atopic dermatitis (ad- justed OR 2.37, 95%CI 1.01;5.72, p=0.048) had significant asso- ciation with the degree of asthma. Conclusion Of 146 children who still had asthma until the age of seven, there were 69% with rare episodic asthma, 26% with fre- quent episodic asthma, and 4.8% with persistent asthma. Factors presumably influencing this manifestations were cigarette smoke exposure, allergic rhinitis, and atopic dermatitis